Effectiveness of Proportional Systems in Legislative General Elections In Legal Politics Perspective - Ichsan Maulana; Gary Gagarin Akbar, Muhamad; Abas, Muhamad; Hidayat, Anwar (Journal of Law, Politic and Humanities, 2024)
The system used in the Indonesian Election is an open proportional system and a closed proportional system. The open proportional system that makes the winner of the most votes in the election creates an unfair competitive atmosphere between legislative candidates, this system dominates the practice of money politics and so on, the closed proportional system also has bitter experiences, the journey of elections since the New Order to the reformation which uses a closed proportional system based on serial numbers is considered to only produce people's representatives who are closer to the interests of political party elites and their groups who have personal interests. Legal Politics has a very important role as a basis for perspective in increasing the effectiveness of national legal development. This study uses descriptive and empirical socio-legal or non-doctrinal methods, applying special legal science research that combines legal norms with sociological aspects through the approach of legal principles and political behavior. To bring elections to an ideal level within the framework of democracy is not only limited to the election system, but must be in line with the awareness of moral values ??upheld by every citizen, both voters and election contestants. Therefore, an appropriate framework of thought is needed with the principle of appreciation in every norm of life. The open proportional system is more relevant to the principle of people's sovereignty, but improvements are needed to the mechanisms and technical provisions in its implementation. Improvements to the open proportional system are important to ensure that this system can run effectively and democratically.